2006
DOI: 10.1103/physrevd.73.102001
|View full text |Cite
|
Sign up to set email alerts
|

Principal component analysis for LISA: The time delay interferometry connection

Abstract: Data from the Laser Interferometer Space Antenna (LISA) is expected to be dominated by frequency noise from its lasers. However the noise from any one laser appears more than once in the data and there are combinations of the data that are insensitive to this noise. These combinations, called time delay interferometry (TDI) variables, have received careful study, and point the way to how LISA data analysis may be performed. Here we approach the problem from the direction of statistical inference, and show that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 21 publications
1
40
0
Order By: Relevance
“…In coherent control, measurement is usually regarded as having deleterious effects. Recent results have shown that quantum measurements can be combined with unitary transformations to complete some quantum manipulation tasks and enhance the capability of quantum control [41], [49], [50]- [55]. For example, Vilela Mendes and Man'ko [41] showed that nonunitarily controllable systems might become controllable by using "measurement plus evolution".…”
Section: The General Methodsmentioning
confidence: 99%
“…In coherent control, measurement is usually regarded as having deleterious effects. Recent results have shown that quantum measurements can be combined with unitary transformations to complete some quantum manipulation tasks and enhance the capability of quantum control [41], [49], [50]- [55]. For example, Vilela Mendes and Man'ko [41] showed that nonunitarily controllable systems might become controllable by using "measurement plus evolution".…”
Section: The General Methodsmentioning
confidence: 99%
“…However, the assumption of constant L is too restrictive, since L can be manipulated by adjusting the state of the environment through its temperature, pressure, or more generally through its distribution function (spectral density). Control through adjusting the state of the environment in general does not preserve quantum coherence in the controlled system and for this reason is called incoherent [3].…”
Section: Coherent and Incoherent Controlsmentioning
confidence: 99%
“…Controlled manipulation by atoms and molecules using external controls is an active field of modern research with applications ranging from selective creation of atomic or molecular excitations out to control of chemical reactions or design of nanoscale systems with desired properties. The external control may be either coherent (e.g., a tailored laser pulse [1]) or incoherent (e.g., a specially adjusted or engineered environment [2,3] or quantum measurements commonly used with and sometimes without feedback [4]).…”
mentioning
confidence: 99%
“…In [34], the authors discussed the clock-noise calibration of the phase fluctuations of the onboard ultrastable oscillators for the second generation formulation of TDI. For more discussion on TDI algorithm and its application to LISA, please see [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] and references therein.…”
Section: Introductionmentioning
confidence: 99%